The engineer Leonardo and the Leonardo engineer: designing rotorcraft under his name five centuries later - Bianco Mengotti, R.; Brughera, P. (My University, 2017)
The fact that, five hundred years after his death, Leonardo da Vinci’s work is still producing admiration, debates, subjects for movies and, closer to us, inspiration for the industry, shows how important and persisting the Italian inventor’s legacy is. Born in a small village in Tuscany in 1452 as love child of Ser (Sir) Pietro da Vinci, Leonardo arrived in Florence as a self-educated boy and started there his polyhedral activity as painter apprentice. In this period he became proficient not only in painting but also in the drawing techniques, and familiarizing himself with classical subjects as well as with architecture, mechanics and sculpture, developing his characteristic approach to the reality. After starting his career as a painter, Leonardo widened his activities to engineering and architecture, mostly working as a consultant –as we would say today- for the most important Lords of the period. In 1482 he introduced himself to the Duke of Milan preparing a presentation [Cod. Atl.] of his skills, ranging from engineering to architecture, from military construction to hydraulics, as well as painting and sculpture. Leonardo da Vinci died in 1519 in Amboise, were he spent his last years working for the king of France as a researcher, architect and painter. Attracted by the theoretical aspects of mathematics and physics, he always paid attention to the applications of his inventions, representing one of the first examples of modern innovators and showing at the same time attitudes typical of today’s hi-tech entrepreneurs. Most of this inventor’s work was collected in a series of notebooks, in which a huge number of drawings, sketches, renderings and annotations keep revealing not just the products of his mind but also a surprisingly modern technical mentality. Thousands of books and articles have been written about Leonardo Da Vinci, touching on his complex personality, his unique skills and his modern attitude. Hundreds of books have been dedicated to the inventor Leonardo Da Vinci, conceiving wings, parachutes, tanks and of course helicopters. But today a new smalltile can be added to this rich mosaic; a perspective which is on one hand personal but at the same time is also more or less shared amongst thousands of people in Europe and in the World. The choice of the Leonardo name by a company provokes its employees to face the values and the ideas connected to the great man. And the fact that in some cases the Leonardo name has substituted very old and famous brands makes this perspective also difficult. So today, in the Leonardo helicopter design group, there are engineers conceiving new air vehicles as the great inventor did five centuries before them. This article is an attempt to discover and to discuss the attitudes, principles and even the techniques followed by these engineers daily, which reflect more or less immediately the Da Vinci vision, perhaps even without their knowledge.